2018
DOI: 10.12688/gatesopenres.12758.2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycobacterium tuberculosis bacilli in bio-aerosols from untreated TB patients

Abstract: Tuberculosis (TB) is predominantly an airborne disease. Background However, quantitative and qualitative analysis of bio-aerosols containing the aetiological agent, , has proven very Mycobacterium tuberculosis (Mtb) challenging. Our objective is to sample bio-aerosols from newly diagnosed TB patients for detection and enumeration of bacilli. Mtb : We monitored each of 35 newly diagnosed, GeneXpert Methods sputum-positive, TB patients during 1 hour confinement in a custom-built Respiratory Aerosol Sampling Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 31 publications
2
63
0
Order By: Relevance
“…As the advantage of ddPCR in the detection of target genes, the application of ddPCR in some tumor oncogenic gene test is now in the clinical registration stage [21] . Previously, studies also showed the application of digital PCR in TB detection using a different type of samples, such as MTB strains [22] , patient plasma [23] , human respiratory aerosol [24] , monkey blood [25] and human sputum [26] . Suporn Pholwat compared Real-time PCR, Sanger Sequencing and Digital PCR using stable extensively drug resistant (XDR) MTB strains.…”
Section: Discussionmentioning
confidence: 99%
“…As the advantage of ddPCR in the detection of target genes, the application of ddPCR in some tumor oncogenic gene test is now in the clinical registration stage [21] . Previously, studies also showed the application of digital PCR in TB detection using a different type of samples, such as MTB strains [22] , patient plasma [23] , human respiratory aerosol [24] , monkey blood [25] and human sputum [26] . Suporn Pholwat compared Real-time PCR, Sanger Sequencing and Digital PCR using stable extensively drug resistant (XDR) MTB strains.…”
Section: Discussionmentioning
confidence: 99%
“…The work we present here pushes beyond the EBC collection to capture particulate matter emanating from the lungs 22 . This exhaled breath aerosol (EBA) sample collection technique was developed to capture bioaerosol particles which contain lung surfactant and microparticle fractions associated with the transmission of infectious diseases 11,12 . EBA-based collection methods offer several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Since EBA sampling methods focus on aerosol particles, study participants do not necessarily make direct contact with the sampling apparatus and saliva/sputum contamination can be avoided during the sample collection . The respired aerosol particles are also analyzed using optical scatter spectrometers to provide a quantitative aerosol particle size distribution that enables sampling standardization 11,12 . In our previous study, we developed an aerosol sampling system, respiratory aerosol sampling chamber (RASC), for the isolation and collection of breath aerosol particles 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations